2015
DOI: 10.1055/s-0034-1399147
|View full text |Cite
|
Sign up to set email alerts
|

CEUS in Hepatocellular Carcinoma and Intrahepatic Cholangiocellular Carcinoma in 320 Patients – Early or Late Washout Matters: A Subanalysis of the DEGUM Multicenter Trial

Abstract: ICCs are rare in cirrhotic livers. CEUS can demonstrate differences in the vascularization patterns between HCC and ICC. HCC showed an arterial global hyperenhancement and delayed contrast washout in the late phase. ICCs are characterized by an arterial contrast enhancement at the tumor periphery with early contrast washout of the vascularized parts of the lesions in the portal-venous and late phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
81
3
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 17 publications
7
81
3
11
Order By: Relevance
“…In the study of Chen et al CEUS showed the same accuracy as CECT [65]. In a subanalysis of the DEGUM study, CEUS managed a correct diagnosis for ICC in 95.2% of cases [66]. According to a Chinese study, most ICCs (87.9%) show "wash-out" in the first 60 seconds, and all of them 3 minutes after the contrast bolus [67] and, based on these criteria, CEUS had 78.8% sensitivity, 88% specificity and 84.3% accuracy for diagnosing ICC [68].…”
Section: Livermentioning
confidence: 88%
“…In the study of Chen et al CEUS showed the same accuracy as CECT [65]. In a subanalysis of the DEGUM study, CEUS managed a correct diagnosis for ICC in 95.2% of cases [66]. According to a Chinese study, most ICCs (87.9%) show "wash-out" in the first 60 seconds, and all of them 3 minutes after the contrast bolus [67] and, based on these criteria, CEUS had 78.8% sensitivity, 88% specificity and 84.3% accuracy for diagnosing ICC [68].…”
Section: Livermentioning
confidence: 88%
“…Otherwise, further percutaneous biopsy or radiofrequency ablation (RFA) will always be guided by real-time BMUS. Short-term BMUS follow-up may be needed to further characterize the lesion [3]. Previous study showed the detection and characterization ability of BMUS is higher if the lesion detected with CT is >5 mm [3].…”
Section: Introductionmentioning
confidence: 99%
“…Short-term BMUS follow-up may be needed to further characterize the lesion [3]. Previous study showed the detection and characterization ability of BMUS is higher if the lesion detected with CT is >5 mm [3]. However, BMUS still shows low specificity and low accuracy for optimal characterization of small FLLs [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, rejecting CEUS as a diagnostic technique would lead to more biopsies including the respective risk and less benefit. In addition, ICCs are relatively rare in cirrhotic livers (1-2% of all new nodules) and CEUS can even show differences in the vascularization patterns between HCC and ICC [22]. HCC shows an arterial global hyperenhancement and delayed contrast wash-out in the late phase.…”
mentioning
confidence: 99%
“…In addition, since the evaluation of cirrhotic patients is performed by applying multimodality imaging strategy, CT and MRI have to be performed. As reported by D'Onofrio et al, the behavior of ICC at CEUS is different from the one in CT. During the late phase, ICC appears hypervascular at CT, because of desmoplastic reaction due to fibrotic component, while at CEUS it appears hypovascular [22]. In these cases CEUS should not be used as the sole imaging technique for conclusive hepatocellular carcinoma diagnosis and if the MRI does not display the diagnostic vascular pattern, a confirmatory biopsy is mandatory [20].…”
mentioning
confidence: 99%